(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Proportional-Integral (PI) controllers are currently used in several industrial processes for controlling the process parameters. In this work a method has been formulated to design the controller for a multi input and multi-output (MIMO) unstable system by considering its effective transfer function (ETF). The approach mentioned, separates the unstable poles of the system into independent loops of the MIMO process with their own ETF’s. The process considered is First Order Process with Time Delay (FOPTD) and PI controllers are modelled for their diagonal components by using ETF synthesis method to counteract unstable characteristics. The design has a two-loop architecture in order to minimize the overshoot, as it is evident that the overshoot is maximum for unstable processes having a single control feedback structure. The controller design is tested for its efficacy on a Two Input Two Output (TITO) system and the results are highlighted for servo as well as regulatory response.